On the energy harvesting and heat transfer ability of a ferro-nanofluid oscillating heat pipe. (April 2019) - Monroe, J. Gabriel; Kumari, Swati; Fairley, John D.; Walters, Keisha B.; Berg, Matthew J.; Thompson, Scott M.
Highlights: A ferro-nanofluid oscillating heat pipe (OHP) was used to generate voltage. Marked improvement in OHP heat transfer occurred (∼70%) when using ferro-nanofluid. A bias magnetic field is needed to locally magnetize suspended ferro-nanoparticles. Energy harvesting via ferrofluidic induction can decrease OHP heat transfer. Abstract: A unique thermal-to-mechanical-to-electrical energy conversion process is demonstrated via thermally-excited, pulsating ferro-nanofluid within a solenoid-equipped oscillating heat pipe ( i.e., ferrofluid-OHP or FF-OHP). The FF-OHP was charged with an aqueous cobalt ferrite ferro-nanofluid, comprised of custom-synthesized CoFe2 O4 nanoparticles surface-modified with citric acid for increased suspensibility. Annular bias magnets were placed directly above and below the FF-OHP solenoid to temporarily magnetize the internal, oscillating ferrofluid. During FF-OHP operation, a measured peak-to-peak voltage of ∼2 mV was measured across the solenoid due to electromagnetic induction. When filled with ferro-nanofluid, the OHP heat transfer was enhanced (relative to pure water) by ∼58% with bias magnets and ∼71% without bias magnets. A maximum effective thermal conductivity of 12.9 kW/m·K was achieved in the FF-OHP at ∼470 W of heat input. With the bias magnets installed ( i.e., harvesting configuration), the FF-OHP effective thermal conductivity was ∼11% lower than when the bias magnets were not present, and this is attributed to an increase in ferrofluid viscosity due to particle magnetization in the bias field. The FF-OHP/solenoid harvesting process is a novel means for accomplishing thermal-to-electrical energy conversion while maintaining high heat transfer capabilities and extreme temperature functionality.